Institutional Capacity as Prevention of Abuse of Power of National Standard Policies for Private Universities in Jakarta - Rozikin, Mochammad; Sofyan, Mohamad; Riyadi, Bambang Slamet; Supriyono, Bambang (International Journal of Criminology and Sociology, 2021)
Research on this journal ontology that many private higher education institutions in Jakarta cover the impact of the policies of the Ministry of Research, Technology and Higher Education of the Republic of Indonesia as public officials to make and issue regulations that are very burdensome for the management of private higher education institutions. The purpose of this research is to criticize for improvement to the government of the Republic of Indonesia. This research used a qualitative method, while the research object was private universities in Jakarta that lack resources. The research subjects were resource persons who were aware of the constraints of the bankruptcy of private universities in Jakarta. The results of the study show that it has been proven that the state, in this case, the Ministry of Research, Technology and Higher Education of the Republic of Indonesia, makes and issues regulations that are very detrimental to the management of private higher education which is minimal in resources. The suggestion from this research shows that the government, by the constitution of the Republic of Indonesia, must be able to provide resource assistance efforts for private universities that are deficient.